Predictors of Persecutory Ideation: Impact of Hell Anxiety and Demonic Struggle among 100 level Accounting Students of Nasarawa State University Keffi - Tobechi, Uzoigwe; Monday, Akawu (Ridwan Institute, 2023)
Religion has been linked to mental health over the years, but its connection to persecutory ideation remains unclear. In this study, Nassarawa State University students' persecutory ideation is examined in relation to religious characteristics as predictors. A cross-sectional survey design was used in the study. In the study, a sample of 162 individuals was chosen at random from the student body. Both the independent and dependent variables were measured with three standardized tools. The use of multiple regression analysis was used to formulate and test two hypotheses. However, the researchers discovered that students' thoughts of being persecuted were jointly and significantly predicted by both hell anxiety and demonic conflict (F = 4.598, p=0.013, R2 = 0.105, r=0.325). Individually, that demonic struggle had significant contributions to the prediction of persecutory ideation. (R2= 0.342, t=2.844; P < 0.05). Hell, anxiety did not significantly predict persecutory ideation. (R2= -0.043, t=-0.360; P > 0.05). These findings recommended that religious authorities consider. minimizing satanic and hell themes in their sermon and focusing on angels, heaven, forgiveness, and other positive concepts that promote a favorable perspective of God, thereby improving the mental health of its congregation. Additionally, psycho-spiritual therapy on the guidance of one's life by good supernatural beings like angels may assist in lessening religiously insured persecutory thinking